2021
DOI: 10.1016/j.celrep.2021.109720
|View full text |Cite
|
Sign up to set email alerts
|

Proteopathic tau primes and activates interleukin-1β via myeloid-cell-specific MyD88- and NLRP3-ASC-inflammasome pathway

Abstract: SUMMARY Pathological hyperphosphorylation and aggregation of tau (pTau) and neuroinflammation, driven by interleukin-1β (IL-1β), are the major hallmarks of tauopathies. Here, we show that pTau primes and activates IL-1β. First, RNA-sequence analysis suggests paired-helical filaments (PHFs) from human tauopathy brain primes nuclear factor κB (NF-κB), chemokine, and IL-1β signaling clusters in human primary microglia. Treating microglia with pTau-containing neuronal media, exosomes, or PHFs causes IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 85 publications
1
51
1
Order By: Relevance
“…We and others have previously demonstrated that tau and preaggregated tau activates the NLRP3-ASC inflammasome (Ising et al, 2019;Jiang et al, 2021;Stancu et al, 2019). We previously demonstrated a modulatory role of the NLRP3-ASC inflammasome on seeded and non-seeded tau pathology using ASC knockout and pharmacological NLRP3 inhibition in mice (Stancu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We and others have previously demonstrated that tau and preaggregated tau activates the NLRP3-ASC inflammasome (Ising et al, 2019;Jiang et al, 2021;Stancu et al, 2019). We previously demonstrated a modulatory role of the NLRP3-ASC inflammasome on seeded and non-seeded tau pathology using ASC knockout and pharmacological NLRP3 inhibition in mice (Stancu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…It must be considered that different microglia‐dependent processes—in addition to neuronal characteristics—may contribute to modulation of tau pathology. NLRP3 inflammasome activation may contribute to tau pathology by (i) secretion of cytokines (including IL1β) which may affect tau phosphorylation (Bhaskar et al, 2010 ; Ghosh et al, 2013 ; Li et al, 2003 ; Maphis et al, 2015 ), by (ii) inducing ASC speck formation (Venegas et al, 2017 ), (iii) by phagocytosing tau (Ising et al, 2019 ; Jiang et al, 2021 ; Stancu et al, 2019 ) and by (iv) modifying proliferation/cell death/differentiation of microglial populations which can differentially contribute to tau pathology. The overall modulation of NLRP3 on tau pathology will be defined by the resultant effects of these different microglia‐dependent processes, which are modulated by NLRP3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian targets that inhibit rapamycin complex 1 (mTORC1) can inhibit hexokinase 1-dependent glycolysis and caspase-1 activation, which indicates that inflammasome activation of NLRP3 is involved in macrophage metabolism [ 127 ]. Aβ [ 85 , 86 , 87 , 88 ] and tau [ 107 , 108 , 109 , 110 ] can activate NLRP3 of microglia via converting its metabolism into sugar [ 107 , 127 ]. Bradley L. Heckmann et al activated RAW264.7 and BMDM at Aβ is closely related to TREM2 and CD63 [ 128 ].…”
Section: Aβ and Tau As A Regulator Of Microglia Metabolism Reprogrammingmentioning
confidence: 99%
“…When we treated microglia with pathological tau with hyperphosphorylation and aggregation-containing neuronal media, exosomes, or paired-helical filaments from the human tauopathy brain, we observed interleukin-1β (IL-1β) activation, which is dependent on NLRP3, ASC, and caspase-1 ( Jiang et al., 2021 ). The pathological tau burden coexists with elevated IL-1β and ASC in autopsy brains of human tauopathies ( Jiang et al., 2021 ). Reduced ubiquitin-proteasome system activity has been found in patients affected by AD and its malfunction plays a significant role in Aβ accumulation ( Bellia et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%